Innovation and uncertainty in the medical industry: Evidence from the case of Myriad Genetics, Inc. - Stan Veuger; Jeffrey Clemens (American Enterprise Institute (AEI), 2015)
We describe the broad range of uncertainties faced by the developers of medical technologies. Empirically, we estimate the asset market incidence of two realizations of uncertainties we classify as within-market policy risks. The events we analyze concern the intellectual property of Myriad Genetics, Inc., an American molecular diagnostics firm. In July 2013, the Supreme Court invalidated several of Myriad's intellectual property claims. Subsequently, the Center for Medicare and Medicaid Services reevaluated the reimbursements it pays for the services at issue in this patent litigation. We estimate that these events substantially moved Myriad's market capitalization, by just under 25 percent in the case of the Supreme Court's decision and nearly 20 percent in the case of CMS's reimbursement rate re-determination. Myriad's exposure to the realization of these intellectual property risks reflects its unusually high reliance on revenues linked to the services at issue. We discuss the implications of these risks for the total volume of medical innovation and for its organization across firms.
Keywords: A; 330; risk